Hormonal type in the conditions of experimental multiple skeletal trauma - M. L. Lebed; M. G. Kirpichenko; S. N. Bocharov; V. V. Gumanenko; L. V. Rodionova (Acta Biomedica Scientifica)
In experiment reproduced model of multiple skeletal trauma (fracture of bones of right forearm and lift shin) with stabilization of fragments with external fixation devices in 35 Chinchilla rabbits. All manipulations were realized, at general anesthesia. Standard treatment included anesthesia, antibiotic prophyliaxis and. infusion therapy by common method. Decrease of metabolism activity was registered in the first group of laboratory animals at the standard treatment. That's why besided strandard treatment dexamethasone and adrenaline in average recommended doses was prescripted in the second group of rabbits in postoperative period for correction of posttraumatic hypobiosis. Laboratory control in several hours after the injection confirmed stable increase of level of corticosteroids in blood but it wasn't possible to register increase of concentration of adrenaline. Correlation analysis was realize to study the connection between the contentration of endogenous hormones in blood and. metabolism activity in rabbits in conditions of multiple skeletal trauma. At the consideration data as one array we determined high-significant (р < 0,001) direct moderate correlation between the values of rectal temperature and. the concentration of free thyroxine in blood (rs = 0,414), this connection was strong on the 3rd day after trauma (rs = 0,833; р < 0,001). Also indirect moderate correlation between values of rectal temperature and. the concentration of cortisol in blood of laboratory animals was registered (rs = 0,49; р < 0,001). The results of study of influence of adrenaline and. noradrenaline on the indices of metabolism activity weren't statistically significant. Obtained data allowed to make a conclusion about importance of endocrine activity of thyroid gland in the formation of adaptation strategy.